The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1088/1475-7516/2017/01/028
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on interacting dark energy models from Planck 2015 and redshift-space distortion data

Abstract: Abstract. We investigate phenomenological interactions between dark matter and dark energy and constrain these models by employing the most recent cosmological data including the cosmic microwave background radiation anisotropies from Planck 2015, Type Ia supernovae, baryon acoustic oscillations, the Hubble constant and redshift-space distortions. We find that the interaction in the dark sector parameterized as an energy transfer from dark matter to dark energy is strongly suppressed by the whole updated cosmo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
118
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 46 publications
15
118
0
2
Order By: Relevance
“…Percival et al 2004;Davis et al 2011;Feix et al 2015;Huterer et al 2017;Adams & Blake 2017). Moreover, it has been shown that RSD provide a powerful probe to constrain the mass of relic cosmological neutrinos (Marulli et al 2011;Upadhye 2019) and the main parameters of interacting DE models (Marulli et al 2012a;Costa et al 2017), as well as helping in breaking the degeneracy between modified gravity and massive neutrino cosmologies (Moresco & Marulli 2017;Wright et al 2019;García-Farieta et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Percival et al 2004;Davis et al 2011;Feix et al 2015;Huterer et al 2017;Adams & Blake 2017). Moreover, it has been shown that RSD provide a powerful probe to constrain the mass of relic cosmological neutrinos (Marulli et al 2011;Upadhye 2019) and the main parameters of interacting DE models (Marulli et al 2012a;Costa et al 2017), as well as helping in breaking the degeneracy between modified gravity and massive neutrino cosmologies (Moresco & Marulli 2017;Wright et al 2019;García-Farieta et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These values of the interaction parameters were chosen so as to maximise the effects of the interaction while at the same time respecting the constraints obtained in Refs. [31,32], which we took as guidelines. The evolution for each model was computed by setting the same initial conditions for all models well inside the past DM-dominated era and numerically integrating the evolution equations.…”
Section: Distinguishing Interactionsmentioning
confidence: 99%
“…Alternatively, one can take into account modifications of the standard cold DM scenario, including a cannibal dark matter [17], partially acoustic dark matter models [18], dissipative dark matter models [19], hot axions [20], charged DM with chiral photons [21] and decaying DM scenarios [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], etc., which provide other possible solutions to resolve the tensions. Moreover, DM self-interactions [37] and DM-DE interacting models [38][39][40][41][42][43][44][45][46][47][48][49] as well as the modified gravity [50,51] are also possible solutions to fix such the tensions.…”
Section: Introductionmentioning
confidence: 99%